2006
DOI: 10.1203/01.pdr.0000219122.81734.03
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant Protein D Levels in Umbilical Cord Blood and Capillary Blood of Premature Infants. The Influence of Perinatal Factors

Abstract: Surfactant protein D (SP-D) is a collectin that plays an important role in the innate immune system and takes part in the surfactant homeostasis by regulating the surfactant pool size. The aims of this study were to investigate the values of SP-D in umbilical cord blood and capillary blood of premature infants and to relate the levels to perinatal conditions. A total of 254 premature infants were enrolled in the present study. Umbilical cord blood was drawn at the time of birth and capillary blood at regular i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 41 publications
(49 reference statements)
1
17
0
Order By: Relevance
“…In accordance with others, 19 our data suggest a postnatal increase in circulating SP-D concentrations, probably due to the physiological reabsorption of lung liquid across the pulmonary epithelium to the circulation during initiation of breathing. 43 Furthermore, we found higher neonatal SP-D concentrations compared with maternal ones.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In accordance with others, 19 our data suggest a postnatal increase in circulating SP-D concentrations, probably due to the physiological reabsorption of lung liquid across the pulmonary epithelium to the circulation during initiation of breathing. 43 Furthermore, we found higher neonatal SP-D concentrations compared with maternal ones.…”
Section: Discussionsupporting
confidence: 93%
“…38 Furthermore, experimental and clinical data suggest increased SP-D expression after glucocorticoid treatment both in vivo and in cultured tissue. 39 However, a previous study 19 including premature IUGR infants demonstrated lower umbilical cord blood SP-D concentrations. The authors speculated that the decreased production of total lung fluid (due to diminished amount of substrates) 7 may account for this result.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Numerous studies use ELISA technique as a means of quantifying SP-D (Postle et al, 1999;Hull et al, 1997;Dahl et al, 2006;Hohwy et al, 2006;Ooi et al, 2007). In this study Western blots on samples of cleaved rfhSP-D reveal that the antibody used (raised against the CRD and thus recognising both NhSP-D and rfhSP-D) recognises cleavage products of rfhSP-D from all 4 enzymes (Fig.…”
Section: Resultsmentioning
confidence: 75%